RISK ASSESSMENT THROUGH MATRIX MODEL IN INSURANCE COMPANIES - Drljača, Dejan S (Poslovna ekonomija, 2017)
Establishment of the Risk Management System and Own Risk and Solvency Assessment in insurance companies, apart from implementation of a set of models, which ensure measurement of potential losses and assessment of the risk size, implies prior definition of risk priorities and limits for risk assumption, as well as periodical review of framework for risk recognition, measurement and assessment. Thus, optimal allocation and use of available financial, technical, information, human and all other available resources is ensured. When determining the procedures and establishing appropriate risk management organization, the insurers firstly select, at the first hierarchy level, models for quantification of possible losses, test the adequacy of calculated technical reserves by using the Liability Adequacy Test and assess levels of individual risks. At the second hierarchy level, they select models for measurement and assessment of solvency, i.e. assessment of capital adequacy and choice of models for assessment of overall exposure at the level of a company as a whole, among which the central place is taken by the matrix model. A matrix model ensures a documented and systematic approach to risks by providing information comparable in time and partially among the insurance companies themselves.